PERBEDAAN SENAM OTOT MATA DENGAN TEKNIK 20-20-20 RULE TERHADAP COMPUTER VISION SYNDROME PADA MAHASISWA STIKES SANTO BORROMEUS - Florentina Dian Maharina; Yohana Hesti Oktania Meliani; Friska Sinaga; Elizabeth Ari Setyarini; Lidwina Triastuti Listianingsih (Jurnal Kesehatan, 2023)
Computer Vision Syndrome which is one of the eye health problems that arise in the world for society. According to Occupational Health Hazard in the 21st century, Computer Vision Syndrome is the number one disease and a danger to workers in front of the computer. The purpose of this study is to find out the difference between eye muscle gymnastics and the 20-20-20 rule technique against Computer vision Syndrome in STIKes Santo Borromeus Students. Computer vision syndrome is a symptom caused by eye vision for laptop use on a monitor for too long. The design of the study used pre-experimental. Purposive sampling technique with a total of 60 respondents, 30 respondents to the eye muscle gymnastics experiment and 30 respondents to the 20-20-20 rule technique experiment. The instrument uses computer vision syndrome- quesionare (cvs-q) with the results of pre-test research from two groups p value = .004 meaning that there is a difference in eye muscle gymnastics with the technique 20-20-20 rule against computer vision syndrome in STIKes santo borromeus students, while for post-test two experimental groups p value = .962 means that there is no difference in eye muscle gymnastics with the technique 20-20-20 rule to computer vision syndrome in STIKes Santo Borromeus students. The advice for STIKes Santo Borromeus can make eye muscle gymnastics as a special eye exercise in students who experience computer vision syndrome